2016
DOI: 10.1007/s00296-016-3444-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and regulatory perspectives on biosimilar therapies and intended copies of biologics in rheumatology

Abstract: Biologics are vital to the management of patients with rheumatic and musculoskeletal diseases such as rheumatoid arthritis and other inflammatory and autoimmune conditions. Nevertheless, access to these highly effective treatments remains an unmet medical need for many people around the world. As patents expire for existing licensed biologic (originator) products, biosimilar products can be approved by regulatory authorities and enter clinical use. Biosimilars are highly similar copies of originator biologics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 60 publications
(73 reference statements)
0
77
0
1
Order By: Relevance
“…Similar to most other countries in the region such as Pakistan and India, it possesses well-structured regulatory pathways for the approval of pharmaceuticals [16]. Under the current national policy, raw materials locally manufactured are protected by restrictions on their import unless adequate quantity of the material is present within the local industry.…”
Section: Case Study: Bangladesh Pharmaceutical Industrymentioning
confidence: 99%
“…Similar to most other countries in the region such as Pakistan and India, it possesses well-structured regulatory pathways for the approval of pharmaceuticals [16]. Under the current national policy, raw materials locally manufactured are protected by restrictions on their import unless adequate quantity of the material is present within the local industry.…”
Section: Case Study: Bangladesh Pharmaceutical Industrymentioning
confidence: 99%
“…43 Non-comparable biotherapeutics have also been referred to as “biomimics” and “intended copies” (the term we use hereafter). 44 In some cases, these products have been licensed prior to the implementation of biosimilar guidelines, via regulatory pathways not appropriate for biologics, such as those used for generic drugs. 43,44 Unlike biosimilars, intended copies lack clear evidence of similarity in quality, safety, and efficacy to the corresponding originator biologic.…”
Section: Biosimilarity: Overview Of Fundamental Principlesmentioning
confidence: 99%
“…2,16,44,57 A 2016 systematic literature review found that most comparative studies reported for such intended copies were either analytical, non-clinical, or observational in nature; as such, there remains a significant dearth of published data demonstrating the safety and efficacy of these agents. 16 …”
Section: Biosimilars In Latin America: Current Situationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the FDA was quick to highlight that it was not approved as an interchangeable product and instead, is merely an option that could potentially expand access to treatment for patients. 3 The American College of Rheumatology (ACR) applauded the decision citing a potential cost savings for patients, but they also expressed concerns over the need for distinct names and transparent labeling for all biosimilar products to ensure correct prescribing and dispensing, post-marketing surveillance, prescriber confidence and enhanced market uptake. There are over 700 biosimilar products in preclinical and clinical trials.…”
mentioning
confidence: 99%